2015
DOI: 10.1016/j.soilbio.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of paddy soil methanotrophs from long term drought

Abstract: a b s t r a c tAir-dried paddy soils stored for 1e18 years were used to examine the resistance of methanotrophs to drought. Older air-dried soils representing longer-lasting drought events reduced methanotrophic diversity, and adversely affected methane oxidation rate after re-wetting. In early incubations the type II methanotrophs are outperformed by the less abundant type I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…The elevated methane uptake in response to severe disturbance in cycles two and three ( Figure 1 ) is noteworthy, but remains to be fully elucidated. Previous studies showed the remarkable resilience of methanotrophic activity to distinct physical disturbances (e.g., disturbance-induced mortality; Ho et al, 2011a , heat stress; Whittenbury et al, 1970 ; Ho and Frenzel, 2012 ; prolonged drought; Collet et al, 2015 , grinding; Kumaresan et al, 2011 ). These disturbances, however, were induced as a single event, and the response of methane uptake and the methanotrophic community composition were monitored during recovery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevated methane uptake in response to severe disturbance in cycles two and three ( Figure 1 ) is noteworthy, but remains to be fully elucidated. Previous studies showed the remarkable resilience of methanotrophic activity to distinct physical disturbances (e.g., disturbance-induced mortality; Ho et al, 2011a , heat stress; Whittenbury et al, 1970 ; Ho and Frenzel, 2012 ; prolonged drought; Collet et al, 2015 , grinding; Kumaresan et al, 2011 ). These disturbances, however, were induced as a single event, and the response of methane uptake and the methanotrophic community composition were monitored during recovery.…”
Section: Resultsmentioning
confidence: 99%
“…Inducing disturbances as single events, aerobic methanotrophs showed remarkable resilience to prolonged drought ( Collet et al, 2015 ), heat stress ( Whittenbury et al, 1970 ; Ho and Frenzel, 2012 ), soil structural disruption ( Kumaresan et al, 2011 ), and a disturbance-induced motility, monitoring re-colonization after a simulated die-off ( Ho et al, 2011a ; Pan et al, 2014 ). Although diversity decreased after disturbance, methanotrophic activity was not adversely compromised, and was even over compensated during recovery when compared to the un-disturbed community ( Ho et al, 2011a ; Kumaresan et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…These will respond with a temporal succession of species (Collet et al. , Ho et al. , b), a process that will only stabilize function through time if a sufficiently diverse pool of taxa is available.…”
Section: Discussionmentioning
confidence: 99%
“…Methanotroph diversity may buffer ecosystem functioning during environmental fluctuations [58][59][60]. Methanotrophs isolated from environmental samples typically exhibit distinct temperature optima.…”
Section: Discussionmentioning
confidence: 99%